2022
DOI: 10.3390/pharmaceutics14010150
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B PET Imaging in Response to In Situ Vaccine Therapy Combined with αPD1 in a Murine Colon Cancer Model

Abstract: Immune checkpoint inhibitors (ICIs) block checkpoint receptors that tumours use for immune evasion, allowing immune cells to target and destroy cancer cells. Despite rapid advancements in immunotherapy, durable response rates to ICIs remains low. To address this, combination clinical trials are underway assessing whether adjuvants can enhance responsiveness by increasing tumour immunogenicity. CpG-oligodeoxynucleotides (CpG-ODN) are synthetic DNA fragments containing an unmethylated cysteine-guanosine motif th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Several studies evaluating granzyme B PET for ICI therapy in different mouse models accurately predicted response to ICI therapy. [76][77][78][79][80][81][82] Granzyme B levels were higher in human melanoma tumors responding to ICI therapy. 78 There is one ongoing clinical trial evaluating granzyme PET with [ 68 Ga]Ga-NOTA-hGZP in patients with melanoma and NSCLC treated with pembrolizumab (NCT04169321), two other trials are listed (NCT04721756, NCT05000372), evaluating [ 18 F]-LY3546117 and [ 68 Ga]Ga-grazytracer respectively for granzyme PET imaging, but not yet recruiting.…”
Section: Il-2 Imagingmentioning
confidence: 97%
“…Several studies evaluating granzyme B PET for ICI therapy in different mouse models accurately predicted response to ICI therapy. [76][77][78][79][80][81][82] Granzyme B levels were higher in human melanoma tumors responding to ICI therapy. 78 There is one ongoing clinical trial evaluating granzyme PET with [ 68 Ga]Ga-NOTA-hGZP in patients with melanoma and NSCLC treated with pembrolizumab (NCT04169321), two other trials are listed (NCT04721756, NCT05000372), evaluating [ 18 F]-LY3546117 and [ 68 Ga]Ga-grazytracer respectively for granzyme PET imaging, but not yet recruiting.…”
Section: Il-2 Imagingmentioning
confidence: 97%
“…CpG-oligodeoxynucleotide (CpG-ODN) is a TLR9 agonist with an immunoactivating effect that can directly induce the activation and maturation of plasmacytoid dendritic cells as an adjuvant for tumor immunotherapy 169 . Studies have shown that CpG-ODNs activate the immune response to tumor cells by inducing the secretion of proinflammatory cytokines such as TNF-α and IL-12 from myeloid cells 170 .…”
Section: Questioning the Impact Of The Gut Microbiota On Cancer Treat...mentioning
confidence: 99%
“…A distinct advantage of using 18 F-tracers, instead of 68 Ga-based tracers, is the improved imaging quality associated with 18 F, and, in addition, the radiation burden is lower despite having a longer half-life, which is also preferable [74,99]. However, 68 Ga is eluted from a generator, 68 Ga yielding [ 68 Ga]Ga-NOTA-GZP [24,96]. The in vitro results indicated that the tracer has high specificity for granzyme B over other granzyme family members, yet selectivity over closely related proteases was not demonstrated [24,97].…”
Section: Granzyme Bmentioning
confidence: 99%
“…Created with BioRender.com.Larimer et al developed a granzyme B-targeted PET activity-based probe (GZP), bearing the granzyme B recognition sequence, Ile-Glu-Phe-Asp, attached to an aldehyde warhead. This ABP contained the radiometal chelator NOTA for radio-labelling with68 Ga yielding [68 Ga]Ga-NOTA-GZP[24,96]. The in vitro results indicated that the tracer has high specificity for granzyme B over other granzyme family members, yet selectivity over closely related proteases was not demonstrated[24,97].…”
mentioning
confidence: 99%